Efektivitas Penggunaan Aplikasi Saku JR dalam Meningkatkan Kinerja Pegawai PT. Jasa Raharja Perwakilan Meulaboh - Oktaviola, Dinda; Safrida, Safrida (Mahesa Research Center, 2022)
This article aims to determine the effectiveness of using the Saku JR application at PT. Jasa Raharja Meulaboh Representative because the JR Saku application was made by an employee of PT. Jasa Raharja Meulaboh Representative and used by employees and officers of SAMSAT work unit representatives of Meulaboh. The problem is focused on the use of the Saku JR application where the Saku JR application is only used by employees and SAMSAT officers of the Meulaboh representative work unit. To approach this problem, Sutrisno's theoretical reference is used, which argues that there are several things that become a benchmark for effectiveness so that it can be said to be effective if it fulfills some of these things. Data was collected through interviews with employees of PT. Jasa Raharja Meulaboh Representative and SAMSAT officer of the Meulaboh representative work unit and analyzed qualitatively. This study concludes that most employees and SAMSAT officers of the Meulaboh representative work unit have used the Saku JR application to help improve services and overcome problems in the field so as to improve their performance, so that it can be said to be effective.